System approach for modeling of the “National Center of the Antarctic Data” portal - N. V. Dermanska; R.L. Novogrudska (Ukrainian Antarctic Journal, 2015)
In work application of system approach for modeling of а portal of National Antarctic Scientific Center as difficult system is offered. System of models of а portal which contains of functional, structural and information models is offered. For representation of each model diagrams with use of the corresponding notations are constructed. On the basis of the offered models structurization of information is carried out, is described functionality of а portal, and also volumes of data flows and the corresponding workflow during its functioning are determined.